Cholesteryl esters of ω-(O-acyl)-hydroxy fatty acids in vernix caseosa - Kalužíková, Aneta; Vrkoslav, Vladimír; Harazim, Eva; Hoskovec, Michal; Plavka, Richard; Buděšínský, Miloš; Bosáková, Zuzana; Cvačka, Josef (Journal of lipid research, 2017)
Cholesteryl esters of ω-(O-acyl)-hydroxy FAs (Chl-ωOAHFAs) were identified for the first time in vernix caseosa and characterized using chromatography and MS. Chl-ωOAHFAs were isolated using adsorption chromatography on silica gel and magnesium hydroxide. Their general structure was established using high-resolution and tandem MS of intact lipids, and products of their transesterification and derivatizations. Individual molecular species were characterized using nonaqueous reversed-phase HPLC coupled to atmospheric pressure chemical ionization. The analytes were detected as protonated molecules, and their structures were elucidated in the negative ion mode using controlled thermal decomposition and data-dependent fragmentation. About three hundred molecular species of Chl-ωOAHFAs were identified in this way. The most abundant Chl-ωOAHFAs contained 32:1 ω-hydroxy FA (ω-HFA) and 14:0, 15:0, 16:0, 16:1, and 18:1 FAs. The double bond in the 32:1 ω-HFA was in the n-7 and n-9 positions. Chl-ωOAHFAs are estimated to account for approximately 1-2% of vernix caseosa lipids.
Keywords: skin lipids; estery cholesterolu; Humans; Vernix Caseosa; mass spectrometry; lipidomics; lidé; mastné kyseliny; novorozenec; neutral lipids; cholesterol; Infant, Newborn; vernix caseosa; Fatty Acids; Cholesterol Esters